Changing values, attitudes and behaviours in Ireland : an analysis of European Social Survey data in Ireland, 2002-2012 /: an analysis of European Social Survey data in Ireland, 2002-2012. (2016) - Breen, Michael J, 1957-; Healy, Amy Erbe
No abstract available